PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN INFLUENCER TERHADAP MINAT BELI KONSUMEN MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PRODUK FACEWASH TERLARIS DI SHOPEE - Apriliana, Alfiyanti; Rizan, Mohamad; Sari, Dewi Agustin Pratama (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The development of digital technology in Indonesia has driven significant changes in people's behavior patterns, especially in buying and selling transactions. In e-commerce, Shopee is indeed one of the most popular platforms among the public. Shopee is an e-commerce application for buying and selling beauty products. From the survey, with the high level of use of this product, it is not surprising that face wash is one of the most frequently purchased skincare products on the Shopee platform, where various choices and prices can be reached by consumers from various circles. Reviews in e-WOM come from ordinary consumers who have used the product or service, while Influencers are individuals who influence the opinions and buying interests of their followers. In general, recommendations made by influencers can build consumer trust and buying interest to try the best-selling face wash products on the Shopee marketplace. This study aims to determine how Electronic Word of Mouth (E-WOM) and Influencers influence consumer buying interest, through trust as a mediator. This study uses a quantitative method with a non-probability sampling technique, especially purposive sampling, with a total of 102 respondents who are active users of Shopee e-commerce in Jabodetabek. Data were collected using a questionnaire, and data analysis was performed using Smart PLS version 4 software.